How to screen for lumbar spine stiffness in patients awaiting total hip arthroplasty - Innmann, Moritz Maximilian; Verhaegen, Jeroen; Renkawitz, Tobias; Merle, Christian; Grammatopoulos, George (The journal of arthroplasty, 2024)
Background: This study aimed to (1) define the prevalence of spinopelvic abnormalities among patients who have hip osteoarthritis (OA) and controls (asymptomatic volunteers) and (2) identify factors that reliably predict the presence of lumbar spine stiffness.Methods: This is a prospective, cross-sectional, case-cohort study of patients who have end-stage primary hip OA, who underwent primary total hip arthroplasty (THA). Patients were compared with a cohort of asymptomatic volunteers, matched for age, sex, and body mass index (BMI), serving as a control group. Spinopelvic pathologies were defined as: lumbar spine flatback deformity (difference of 10 or more degrees for pelvic incidence minus lumbar lordosis angle), a standing sagittal pelvic tilt of 19 degrees or more and lumbar spine stiffness (lumbar flexion of less than 20 degrees between both postures).Results: The prevalence of spinopelvic pathologies was similar between patients and controls (flatback deformity: 16% versus 10%, P = .209; standing pelvic tilt >19 degrees: 17% versus 24%, P = .218; lumbar spine stiffness: 6% versus 5%, P = .827). Age over 65 years-old and standing lumbar lordosis angle less than 45 degrees were associated with high sensitivity and specificity for identifying lumbar spine stiffness (age >65 years: 82% and 66%; standing lumbar lordosis angle <45 degrees: 85% and 73%).Conclusion: The presence of end-stage hip osteoarthritis was not associated with increased prevalence of adverse spinopelvic characteristics compared to matched, asymptomatic volunteers. Age and LLstanding are the strongest predictors of lumbar spine flexion and can guide clinical practice on when to obtain additional radiographs for patients who have hip OA before arthroplasty to identify at-risk patients. Level of Evidence: II (prospective, cohort study). (c) 2023 Elsevier Inc. All rights reserved.